Vitamin B12 Supplementation and NT-proBNP Levels in COPD Patients: A Secondary Analysis of a Randomized and Controlled Study in Rehabilitation - Paulin, Fernanda Viana; Goelzer, Leandro Steinhorst; Müller, Paulo de Tarso (Frontiers in Neuroscience, 2020)
Purpose There is evidence of complex interaction between vitamin B12 (vB12) level, hyperhomocysteinemia, and natriuretic peptide secretion. Exercise training could also modulate such interaction. In this secondary analysis of a Randomized Clinical Trial performed in a chronic obstructive pulmonary disease rehabilitation setting, our primary objective was to investigate the interaction between vB12 supplementation, exercise training and changes in NT-proBNP levels after eight weeks of intervention. Secondary objectives were to explore the correlations between acute changes in NT-proBNP levels with (i) acute exercise and (ii) oxygen uptake (V´O2) kinetics during rest-to-exercise transition. Methods Thirty-two subjects with COPD were randomized into four groups: Rehabilitation+vB12(n=8), Rehabilitation(n=8), vB12(n=8) or Maltodextrin(n=8). They were evaluated at baseline and after eight weeks, during resting and immediately after maximal exercise constant work-rate tests (Tlim), for NT-proBNP plasmatic levels. Results After interaction analysis, the supplementation with vB12 significantly changed the time course of NT-proBNP responses during treatment (p=0.048). However, the final analysis could not support a significant change in NT-proBNP levels owing to high-intensity constant work-rate exercise (p-value >0.05). There was a statistically significant correlation between V´O2 time constant and ∆NT-proBNP values (Tlim – rest) at baseline (p=0.049) and two months later (p=0.015), considering all subjects (n=32). Conclusions We conclude that vB12 supplementation could modulate NT-proBNP secretion. Moreover, possibly, the slower the initial V´O2 adjustments toward a steady-state during rest-to-exercise transitions, the more severe the ventricular chamber volume/pressure stress recruitment, expressed through higher NT-proBNP secretion in subjects with larger V´O2 time constants, despite unchanged final acute exercise-induced neurohormone secretion.